Amitraz poisoning: a rare case of suicidal poisoning from Malwa region of Punjab and role of early gastric lavage in preventing complications - Raina, Rohit; Singh, Rajat; Dhoat, Preeti Singh; Kaur, Amandeep; Verma, Niket; Chaudhary, Deepak; Kansal, Maninder (International Journal Of Community Medicine And Public Health, 2024)
Amitraz, a widely-used pesticide for both crops and animals globally, effectively controls pests such as ticks and mites in livestock, as well as red spider mites in fruit crops. Its formulation includes triazapenta 1,4 diene from the formamidine family. Despite its widespread use, only a few cases of poisoning have been reported worldwide, mostly stemming from accidental exposure. We present a case involving a 28-year-old woman from the Malwa region of Punjab, who intentionally ingested 30 ml of amitraz solution (12.5% w/v) following a marital dispute, resulting in a suicide attempt. The patient fully recovered within 72 hours and was discharged with resolved symptoms on the third day. Amitraz poisoning typically occurs due to accidental ingestion. In our case, the patient experienced central nervous system depression accompanied by bradycardia (Figure 1), necessitating treatment with atropine. These effects persisted for 72 hours. The clinical manifestations observed in our patient align with the mechanism of action on alpha 1 and alpha 2 receptors, with dizziness and bradycardia being prominent features. Respiratory involvement is also possible, while liver and renal effects are rare. Early gastric lavage is recommended for managing amitraz poisoning.